Digitization of industrial work: development paths and prospects - Hartmut Hirsch-Kreinsen (Journal for Labour Market Research, 2016)
This paper summarizes considerations and preliminary research results on the consequences of the progressive use of digital technologies in industrial work. The focus is particularly on the situation in German industry, where this development has been intensively discussed as 'Industry 4.0'. Starting point is the assumption that currently a far-reaching technology push in industrial production can be observed. In terms of the potential consequences for industrial labor foreseen by the literature, currently contradictory development scenarios are being discussed. For one thing, the volume of potential job losses caused by the new technologies is highly controversial. For another, diverging consequences for job activities and qualifications can be recognized, interpreted as the 'upgrading', respectively 'polarization' of skills. What concrete changes actually occur however, is dependent on the influence of numerous factors. Especially, what concept of technology automation is realized in each case, and its respective implementation process, is significant here. The conclusion reached is that, in the medium term, at the most a somewhat limited spread of digital technologies and their consequences can be expected to occur.
Keywords: 330; technischer Wandel - Auswirkungen; Industriearbeit; Zukunft der Arbeit; Digitale Arbeitswelt; Produktion - Vernetzung; Szenario; Qualifikationsanforderungen; Automatisierung; Beschäftigungseffekte